Wind Farm Layout Optimization to Maximize Total Power Production - Alabaş Uslu, Çiğdem; ÜLKÜ, İLAYDA (E3S Web of Conferences, 2018)
With the rapid increase in energy demand, renewable energy has been considered as an alternative energy resource around the world. A new nonlinear mathematical model is developed in the presented study and a comparison is obtained with a mathematical modelling study from the literature. The results superior according to power generation under a single wind direction. Jensen’s wake decay model is used to state multiple wake effect among the turbines. The power production is maximized in terms of the minimization of wake effects. Mathematical formulations are represented and compared with the model from the literature. The generated layouts are presented and expected power among the Introduction turbines are significantly improved.